Business issues today : alternative perspectives - Carson, Robert Barry (New York : St. Martin's Press, 1984)
The objective of this book is to bring the current debates over business policy into the introduction-to- business or introduction -to - management classrooms.
Includes bibliographical references p. [343]-345.
hza 04/09/2018
Loans
Keywords: Industrial management; Business enterprises